The Young Turk Movement and its Impact on the Development of Nationalism in Indonesia in the Early 20th Century - Juirah Juirah (Universitas Islam Negeri Sumatera Utara, 2026)
The Young Turk Movement, which ended the Ottoman Caliphate, had a significant impact on the development of nationalism around the world, especially in Indonesia, in the fight against colonialism. It is interesting to study the main movements and ideas of the Young Turks that inspired nationalism in Indonesia, as well as the figures who were influenced by the movement. This study aims to identify the main movements/ideas of the Young Turks that inspired nationalism in Indonesia, as well as the figures whose thoughts were in line with the movement. The research method used is library research by exploring data from literature that examines the Young Turks Movement and the development of nationalism in Indonesia. The results of the study show that the Young Turks Movement inspired the Indonesian people, especially intellectual figures, to carry out a national movement against Dutch colonialism. They used newspapers as a medium to obtain information, make direct contact, and improve education. Several figures whose thoughts were in line with the Young Turks Movement were Ir. Soekarno, Moh. Hatta, KH. Agus Salim, Ki Hajar Dewantara, and Moh. Natsir.